Determination of leachable components from an experimental endodontic sealer by nuclear magnetic resonance (NMR) spectroscopy - Davis Cher H.; Skrtic Drago (Serbian Medical Society - Dental Section, Belgrade, 2011)
Introduction. Studies of experimental composites based on amorphous calcium phosphate (ACP) intended for dental applications as remineralizing pit and fissure sealants, orthodontic adhesives and, most recently, endodontic sealers were mainly focused on improving their mechanical, esthetic and remineralizing capabilities. Similar to the vast majority of commercial composites, these experimental formulations might have clinical drawbacks due to incomplete conversion of monomers and leachability of monomers and degradation products, shrinkage and stress associated with polymerization, and microleakage typically occurring at the tooth/composite interfacial region. The aim of this study was to identify and quantify leachable components from the experimental amorphous calcium phosphate (ACP) endodontic sealer using 1H nuclear magnetic resonance (NMR) spectroscopy. Material and Methods. The light-cure resin [camphorquinone (CQ) + ethyl-4-N,N-dimethylamino benzoate (4EDMAB)] was formulated from urethane dimethacrylate (UDMA), poly(ethylene glycol)- extended urethane dimethacrylate (PEG-U), 2-hydroxyethyl methacrylate (HEMA) and methacryloyloxyethyl phthalate (MEP). The experimental sealer contained 40 mass % ground ACP and 60 mass % resin. The copolymer (unfiled resin) and ACP/UPHM composite specimens, after being dried to a constant mass, were extracted in butylated hydroxyl toluene (BHT; prevents polymerization of eluted components) containing acetone for 7 days at 23ºC with continuous magnetic stirring. Gravimetric changes were recorded for each specimen. After solvent evaporation, 1H NMR spectra were collected on the extractable portion of each specimen. Representative peaks for each component were used to calculate their relative portions in the extracts. By combining the gravimetric and NMR data, the overall loss of each monomer and its concentration in the extract was calculated. Results were statistically analyzed by ANOVA and multiple pair-wise comparisons (t-test). Results. No CQ could be detected in the extracts. However, 33.06 % and 24.66 % of the initially incorporated 4EDMleached from the copolymers and composites, respectively. 0.30-14.29% and 0.12-10.39% of each monomer content leached out from copolymers and composites, respectively. The apparent differences in the concentrations between copolymers and composites became marginal when composite data were normalized with respect to the initial amount of the resin. Conclusion. 1H NMR conveniently provides qualitative and quantitative information on leachables without the elaborate sample preparation and/or data interpretation. Leachability of the unrectaed monomers from the experimental ACP sealer is apparently controlled by the highly cross-linked resin network and unaffected by the incorporation of bioactive ACP into the resin. The maximum levels of leachables from our experimental composite were within or below the concentration ranges reported for the commercial counterparts.